2001
DOI: 10.1074/jbc.m100294200
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal Triglyceride Transfer Protein Binding and Lipid Transfer Activities Are Independent of Each Other, but Both Are Required for Secretion of Apolipoprotein B Lipoproteins from Liver Cells

Abstract: Recent studies indicate that microsomal triglyceride transfer protein (MTP) and apolipoprotein B (apoB) interact physically via two specific binding sites located within the amino-terminal globular region of apoB100. The first site is thought to be within the first 5.8% of the amino-terminal sequence, and the second site is between 9 and 16% of the amino-terminal sequence. It is not clear from prior studies whether these sites have unique or overlapping functions. Furthermore, there are no data differentiating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 38 publications
1
38
0
1
Order By: Relevance
“…MTP is a heterodimeric protein complex possessing lipid transfer activity, which functions in the small intestine and liver to transfer lipids to assist in the formation of primordial apoB lipoproteins. It has been shown to have three domains: 1) an apoB binding domain; 2) a lipid transfer domain; and 3) a membrane association domain [46]. The initial incorporation of lipids into apoB by MTP may prevent apoB from degradation.…”
Section: Apolipoproteins and Chylomicron Synthesismentioning
confidence: 99%
“…MTP is a heterodimeric protein complex possessing lipid transfer activity, which functions in the small intestine and liver to transfer lipids to assist in the formation of primordial apoB lipoproteins. It has been shown to have three domains: 1) an apoB binding domain; 2) a lipid transfer domain; and 3) a membrane association domain [46]. The initial incorporation of lipids into apoB by MTP may prevent apoB from degradation.…”
Section: Apolipoproteins and Chylomicron Synthesismentioning
confidence: 99%
“…It was clearly shown that newly synthesized apoB in cells lacking MTP failed to associate with lipids and subsequently the apoB was degraded (8). It is also reported that MTP has a molecular chaperon-like activity (9) and contributes to TG transfer from cytosol to lumen of the endoplasmic reticulum (10,11).…”
mentioning
confidence: 99%
“…MTP catalyses the assembly of triglyceride-rich plasma lipoproteins (VLDL) and chylomicrons by carrying lipid from endoplasmic reticulum membrane to apoB particles in the lumen of endoplasmic reticulum (Olofsson et al 1999). The assembly of lipoproteins involves a physical binding of apoB and the larger subunit of MTP, but the precise mechanism remains to be elucidated (Bradbury et al 1999;Gretch et al 1996;Liang and Ginsberg 2001;Wetterau et al 1990).…”
Section: Introductionmentioning
confidence: 99%